1980
DOI: 10.2190/x565-hw49-chr0-fyb4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adult Bereavement in the Death of a Spouse, Child, and Parent

Abstract: aBsmacTThe Grief Experience Inventory (GEI) and the MMPI were used to assess bereavement reactions in 102 newly bereaved individuals; 107 controls were also assessed. Intensities of bereavement reactions were compared across three types of deaths experienced, i.e., spouse, child, and parent. Significantly higher intensities of grief were noted in parents surviving their child's death. A distinct number of physiological symptoms were noted in the bereaved group as compared to controls. Frequent church attenders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0
6

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(187 citation statements)
references
References 25 publications
10
171
0
6
Order By: Relevance
“…Observed grief patterns are consistent with the age asymmetries inherent in Hamilton's rule. For instance, Sanders (1979) used a psychological survey instrument, the Grief Experience Inventory, to assess experiences of 102 newly bereaved persons, and found significantly higher intensities of grief on the part of parents surviving a child's death than vice versa. Age-specific values of mortuary remains for a Native American burial site in the American Southwest analyzed in MacDonald (2001) are consistent with more intense grief at the loss of kin whose reproductive value is high.…”
Section: Age Asymmetries In Altruismmentioning
confidence: 99%
“…Observed grief patterns are consistent with the age asymmetries inherent in Hamilton's rule. For instance, Sanders (1979) used a psychological survey instrument, the Grief Experience Inventory, to assess experiences of 102 newly bereaved persons, and found significantly higher intensities of grief on the part of parents surviving a child's death than vice versa. Age-specific values of mortuary remains for a Native American burial site in the American Southwest analyzed in MacDonald (2001) are consistent with more intense grief at the loss of kin whose reproductive value is high.…”
Section: Age Asymmetries In Altruismmentioning
confidence: 99%
“…Studies have shown that the loss of a child leads to more intense and persistent grief and depression than the loss of a sibling, spouse, or parent (Cleiren, 1991;Leahy, 1992;Nolen-Hoeksema & Larson, 1999;Sanders, 1979). Similarly, the loss of a close friend or family member could predict more difficulty than the loss of a colleague or an acquaintance.…”
Section: Interpersonal Mediators and Moderators Of The Grief Responsementioning
confidence: 99%
“…The death of a child can have a devastating effect on parents. Following the death of a child, the grief of parents is particularly severe, long lasting, and complicated with symptoms that fluctuate over time (Rando, 1986;Sanders, 1980). Sanders (1980) compared the intensity of bereavement reactions across three types of death experiences (i.e., spouse, child, and parental) and found that bereaved parents experience more somatization, depression, anger, quilt, and despair than bereaved persons who have lost either a spouse or parent.…”
Section: Reviv Ot the Litraturementioning
confidence: 99%
“…There is an array of opinions in the literature on how long the grieving process lasts. In general, the grief of bereaved parents is particularly intense and long-lasting (Rando, 1986;Sanders, 1980). The grief of fathers is usually less intense and resolves sooner than that of mothers (Cornwell et al, 1977;Helmrath & steinitz, 1978).…”
Section: Parental Grief Reactionsmentioning
confidence: 99%